Resveratrol Attenuates the Release of Inflammatory Cytokines from Human Bronchial Smooth Muscle Cells Exposed to Lipoteichoic Acid in Chronic Obstructive Pulmonary Disease. (30th September 2013) - Knobloch, Jürgen; Wahl, Chiara; Feldmann, Maria; Jungck, David; Strauch, Justus; Stoelben, Erich; Koch, Andrea
Abstract During bacterial infections, pathogen‐associated molecular patterns (PAMPs) induce cytokine/chemokine release in immunoactive cells. This increases corticosteroid‐resistant airway inflammation in chronic obstructive pulmonary disease (COPD) and leads to exacerbations. Anti‐inflammatory therapies other than corticosteroids are required and resveratrol is currently under discussion. Resveratrol is an activator of sirtuins, which are class III histone deacetylases (HDACs). We suggested that human airway smooth muscle cells (HASMCs) release COPD‐associated cytokines/chemokines in response to lipoteichoic acid (LTA), a major PAMP of gram‐positive bacteria and that resveratrol is superior to the corticosteroid dexamethasone in suppressing these cytokines/chemokines. Cultivated HASMCs of patients with COPD were pre‐incubated with resveratrol or dexamethasone before stimulation with LTA. CCL2, GM‐CSF, IL‐6 and IL‐8 were analysed in culture supernatants by enzyme‐linked immunosorbent assay. Drug effects were investigated in the absence and presence of trichostatin A (TSA), an inhibitor of class I/II HDACs, and EX527, an inhibitor of the sirtuin SIRT1. LTA induced robust cytokine/chemokine release. Resveratrol was superior to dexamethasone in reducing CCL‐2, IL‐6 and IL‐8 in LTA‐exposed HASMCs of patients with COPD. Both drugs were equally effective in reducing GM‐CSF. Resveratrol effects were partially reversed by EX527 but not by TSA. Dexamethasone effects were partially reversed by TSA but not by EX527. We conclude that HASMCs contribute to the increase in airway inflammation in COPD exacerbations caused by gram‐positive bacterial infections. Our data suggest resveratrol as an alternative anti‐inflammatory therapy in infection‐induced COPD exacerbations. Resveratrol and corticosteroids suppress cytokine/chemokine expression through activation of SIRT1 or interaction with class I/II HDACs, respectively, in HASMCs.